Vertical intra-industry trade and foreign direct investment between Japan and European Countries - Yoshida, Yushi (2011)
In this paper, we provide an overview of the development of vertical intra-industry trade (VIIT) between Japan and various European countries, including both old and new EU members, as well as emerging Central and Eastern European countries. VIIT indices constructed in this paper cover a much wider range of margins of unit price ratio than existing studies. Our empirical model attempts to explain the distributional characteristics of VIIT through foreign direct investments (FDI), in addition to traditional determinants of IIT, such as differences in GDP per capita, average GDP, and smaller and larger GDPs. Our sample covers the period from 1988 to 2004 for bilateral trade between Japan and 31 European countries. Our econometric methodology for these panel data uses fixed-effect model estimation with a variable transformation determined by a Box-Cox approach. We find that intra-industry trade between European countries and Japan increases with their corresponding Japanese FDIs, especially for new EU member countries. Our results also indicate that it is important to measure a wider range of quality based on relative prices rather than the traditional ratio used in the literature.